PRAKTIK BERBAHASA DISFEMIA DAN KOGNISIS SOSIAL PADA KOMENTAR BERITA PEMILU 2024 - Rangga Agnibaya (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2025)
This study examines language practices occurring in the comment sections of online media, specifically in the comment sections of news articles related to the 2024 Indonesian presidential election. The researcher found that there were instances of dysphemistic language behavior in the majority of comments in the election news comment sections. Using the critical discourse analysis method, the researcher analyzed both the textual and contextual aspects of comments that met the criteria for dysphemistic language practices. The research findings revealed dysphemistic practices carried out by commenters, directed both at the subjects being reported on and at other commenters participating in the discussion. Furthermore, the researcher also identified two social cognitions that underlie the production of dysphemistic comments. These two social cognitions are: (1) Rejecting Prabowo as a proxy for Jokowi; and (2) Presidential and vice-presidential candidates must not have negative sides. The practical contribution of this research is to provide an understanding of the impact of dysphemistic language practices in the comment sections of 2024 presidential election news on readers' social cognition, which can assist in designing more effective communication policies or strategies for managing healthy and constructive online interactions.